Assessment of a New Approach for Systematic Subsurface Drip Irrigation Management - Hédi Ben Ali; Moncef Hammami; Ahmed Saidi; Rachid Boukchina (International Journal of Agronomy)
This paper aimed to assess the reliability of a new approach that provides systematic irrigation management based on fixed water suction in the vadose zone. Trials were carried out in the experimental farm of IRA Gabès on subsurface drip irrigated (SDI) tomato plot. The SDI system was designed so that the soil water content is to be maintained within prescribed interval ascertaining the best plant growth. Irrigation management was systematically monitored by water suction evolution in the vadose zone. Recorded results showed that all-over irrigation season lateral pressure head ranged within 93.3 ± 20.0; 119.95 ± 53.35 and 106.6 ± 40.0 mb, respectively, at the upstream, middle, and downstream. The correspondent lateral pressure head distribution uniformity ranged within 97.1% and 99.6%. Soil water content varied within 0.2175 ± 0.0165; 0.206 ± 0.0195 and 0.284 ± 0.100 beneath the inlet, the behalf, and the lateral end tip. The correspondent soil water distribution uniformity was higher than 80.7% all-over irrigation season. Based on the recorded results, the proposed approach could be a helpful tool for accurate SDI systems design and best water supplies management. Nevertheless, further trials are needed to assess the approach reliability in different cropping conditions.